2018
DOI: 10.5194/acp-18-5953-2018
|View full text |Cite
|
Sign up to set email alerts
|

Particulate matter air pollution may offset ozone damage to global crop production

Abstract: Abstract. Ensuring global food security requires a comprehensive understanding of environmental pressures on food production, including the impacts of air quality. Surface ozone damages plants and decreases crop production; this effect has been extensively studied. In contrast, the presence of particulate matter (PM) in the atmosphere can be beneficial to crops given that enhanced light scattering leads to a more even and efficient distribution of photons which can outweigh total incoming radiation loss. This … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 61 publications
4
44
0
Order By: Relevance
“…Changes in R GR and F diff vary among different regions, and their impacts on crops may depend on crop varieties and other climatic factors. In addition, earlier studies have suggested that global dimming might also have an effect on C 4 crops like maize (Proctor et al, ; Schiferl & Heald, ; Yue & Unger, ). Whether the mechanisms we found here for wheat and rice in our study area apply to other C 3 crops or varieties grown elsewhere, or to C 4 crops merits further investigations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in R GR and F diff vary among different regions, and their impacts on crops may depend on crop varieties and other climatic factors. In addition, earlier studies have suggested that global dimming might also have an effect on C 4 crops like maize (Proctor et al, ; Schiferl & Heald, ; Yue & Unger, ). Whether the mechanisms we found here for wheat and rice in our study area apply to other C 3 crops or varieties grown elsewhere, or to C 4 crops merits further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…When canopy is illuminated more by direct radiation, the upper leaves are easy to reach light saturation, while the leaves at the bottom may be shaded and not receive sufficient radiation for photosynthesis (Kanniah et al, 2013;Williams et al, 2014). In contrast, diffuse radiation allows the lower leaves to receive more radiation, and prevents the upper leaves from reaching light saturation (Gu et al, 2002;Mercado et al, 2009;Schiferl & Heald, 2018). This diminishing return light response shape in combination with differences in canopy light profile between CK and shading treatments contributed to our result that, for both crops, RUE increased under global dimming ( Our experiments revealed an additional, novel mechanism.…”
Section: Causes For the Increased Ruementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the effects of diffuse fraction, we assessed whether heightened [O 3 ] copollutants (Figure , bottom), often associated with wildfire (Jaffe & Wigder, ; Pfister et al, ; Yamasoe et al, ), could have caused diminished ecosystem productivity, counteracting the GEP enhancement due to increased diffuse fraction (Schiferl & Heald, ; Yue & Unger, ). Due to the distance from the fire source of our sites (>100 km) and the complex array of NOx and volatile organic carbon sources and sinks that the smoke plume passed over, attribution of O 3 can be challenging (Jaffe & Wigder, ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lower threshold for light saturation in C 3 versus C 4 photosynthetic pathways (Ehleringer et al, 1997;Pearcy & Ehleringer, 1984), C 3 vegetation may be more sensitive to increased diffuse fraction than C 4 vegetation (Sinclair et al, 1992). Observed crop-or species-specific relationships between diffuse fraction and LUE are necessary to better constrain large-scale models (Schiferl & Heald, 2018;Sinclair et al, 1992).…”
Section: Introductionmentioning
confidence: 99%